2011
DOI: 10.1002/jrs.2728
|View full text |Cite
|
Sign up to set email alerts
|

Effects of solid substrate on the SERS‐based immunoassay: a comparative study

Abstract: A comparative study of the solid substrates used in surface-enhanced Raman scattering (SERS) based immunoassay is made in this paper. Five different substrates were prepared and divided into two groups with and without SERS activity. They are (1) a poly-L-lysine slide, (2) a glutaraldehyde (GA)-aminosilane slide, (3) a substrate assembled with silver nanoparticles, (4) a substrate assembled with silver nanoparticles and functionalized with GA-aminosilane and (5) a substrate assembled with gold nanoparticles, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 39 publications
(34 reference statements)
2
7
0
Order By: Relevance
“…S5c ). Similar results have been observed and detected by the ATR/FTIR technique 23 . Additionally, according to the literature 24 the broadening and the shift to longer wavelength may also indicate aggregation.…”
Section: Resultssupporting
confidence: 90%
“…S5c ). Similar results have been observed and detected by the ATR/FTIR technique 23 . Additionally, according to the literature 24 the broadening and the shift to longer wavelength may also indicate aggregation.…”
Section: Resultssupporting
confidence: 90%
“…A lot of effort has been put towards choosing and optimizing various types of different surfaces in recent years. It has been reported that the SERS effect can be attenuated by various substrates [44]. Thus far, assays have been made using many different solid substrates including glass slides, microtiter plate wells, and filter supports.…”
Section: Capture Substratementioning
confidence: 99%
“…In a typical SERS‐based immunoassay, capture biomolecules or proteins such as antigens are immobilized on a solid substrate. Labeled target molecules bind to their specific capture molecule and the interaction is detected by recording an SERS fingerprint spectrum of the label . Recently, a label‐free in situ detection of microorganisms, for example bacteria, is presented.…”
Section: Immunoassay Based On Sersmentioning
confidence: 99%
“…Here, the SERS signal was generated by the target protein and not from a Raman marker molecule. Various substrates were prepared and it was shown that SERS substrates with assembled silver nanoparticles were the most effective ones for the detection of 4‐mercaptobenzoic acid when excited at 633 nm .…”
Section: Immunoassay Based On Sersmentioning
confidence: 99%